Formation of high aspect ratio TiO2 nanotube arrays by anodization of Ti foil in organic solution - Srimala Sreekantan,; Roshasnorlyza Hazan,; Khairul Arifah Saharudin,; Lai, Chin Wei; Ishak Mat, (Universiti Kebangsaan Malaysia, 2011)
Titanium oxide (TiO2) nanotubes were successfully formed by anodization of pure titanium foil in a standard two-electrode bath consisting of ethylene glycol solution containing 5 wt% NH4F. The pH of the solution was ∼ 7 and the anodization voltage was 60 V. It was observed that such anodization condition results in ordered arrays of TiO2 nanotubes with smooth surface and a very high aspect ratio. It was observed that a minimum of 1 wt % water addition was required to form well ordered TiO2 nanotubes with length of approximately 18.5 μm. As-anodized sample, the self-organized TiO2 nanotubes have amorphous structure and annealing at 500oC of the nanotubes promote formation of anatase and rutile phase. Photocatalytic activity of well ordered TiO2 nanotubes with two different lengths was evaluated by measuring the degradation of methyl orange (MO). The elaboration of this observation is described in detail in this paper.